Analysis Of Factors Affecting The Percentage Of Poverty In West Kalimantan With Panel Data Regression - Dinda Kinanti Ayuningtyas; Khairina Auliannisa; Shantika Martha (Jurnal Forum Analisis Statistik, 2023)
Indonesia has a high poverty rate, which is evidenced by the annual increase in the percentage of people living in poverty. This happens because the components of high life expectancy, as well as the higher level of education, Reducing the poverty rate is closely related to improving the welfare of the community. This has a significant impact on the overall well-being of the community. Therefore, this study aims to determine the best panel data regression model of Life Expectancy and Expected Years of Schooling on the percentage of poor people. The three model approaches tested are Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM). Based on the estimation of panel data regression parameters, it was found that the best model approach to analyze the poverty rate in West Kalimantan in 2018-2022 is the FEM. The F test showed that the result is 0.00 < 0.05. Which means that the Life Expectancy and Expected Years of Schooling variables have a significant influence on poverty rate. the Life Expectancy and Expected Years of Schooling were found to be the variables that influence poverty rate in West Kalimantan, with an adjusted Â value of 98,89%.